2006
DOI: 10.1126/science.1125237
|View full text |Cite
|
Sign up to set email alerts
|

Synchrony, Waves, and Spatial Hierarchies in the Spread of Influenza

Abstract: Quantifying long-range dissemination of infectious diseases is a key issue in their dynamics and control. Here, we use influenza-related mortality data to analyze the between-state progression of interpandemic influenza in the United States over the past 30 years. Outbreaks show hierarchical spatial spread evidenced by higher pairwise synchrony between more populous states. Seasons with higher influenza mortality are associated with higher disease transmission and more rapid spread than are mild ones. The regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

51
881
7
7

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 785 publications
(978 citation statements)
references
References 28 publications
51
881
7
7
Order By: Relevance
“…A/H1N1 viruses have intermediate evolutionary rate [59] and did not display a clear relationship with transmissibility in our study. Our finding of increased transmissibility of A/H3N2 viruses reinforces a recent study showing more rapid dispersal of A/H3N2 epidemics across the United States, as compared with A/H1N1-B epidemics [18].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…A/H1N1 viruses have intermediate evolutionary rate [59] and did not display a clear relationship with transmissibility in our study. Our finding of increased transmissibility of A/H3N2 viruses reinforces a recent study showing more rapid dispersal of A/H3N2 epidemics across the United States, as compared with A/H1N1-B epidemics [18].…”
Section: Discussionsupporting
confidence: 89%
“…Past studies have estimated the reproduction number of individual influenza seasons, in particular for pandemics [11][12][13][14][15][16][17][18][19]. However, no study has yet reported estimates of the reproduction number for several countries and consecutive influenza seasons in the interpandemic period, where a fraction of the population is immune due to previous influenza exposure or vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…This suggests that cities with different mobility patterns may also differ in the rate at which their inhabitants have infectious contact, leading to variation among cities in the risk of an epidemic [5][6][7]. Human movement patterns are heterogeneous at a wide range of scales-from within a building [8] to among countries [9][10][11], as evidenced by diverse sources of data, including the movements of mobile phone users [12,13], air travel patterns [9][10][11] and census data on commuting patterns [10,14,15]. At each scale, there appear collective mobility patterns maintained far from those predicted by homogeneous random movement.…”
Section: Introductionmentioning
confidence: 99%
“…Individual variation in rates of infectious contact can significantly alter patterns of disease spread [6,7,15,[19][20][21] and theoretical models of disease dynamics within and among cities (both individual-based simulations [5,7,10,15,[22][23][24] and metapopulation models [10,11,14,15,[25][26][27]) have shown that heterogeneous contact patterns are potentially important in determining urban epidemic dynamics. However, few studies have examined whether empirical variation in intracity mobility patterns is sufficient to drive detectable differences in epidemic dynamics among cities.…”
Section: Introductionmentioning
confidence: 99%
“…Commuting destinations for both workers and students are randomly assigned by employing a gravity model (Viboud et al, 2006), integrated with specific data (ISTAT, 2001b).…”
mentioning
confidence: 99%